A devolução das quantias pagas pelos consumidores desistentes e excluídos dos contratos de consórcio à luz da Lei 11.795/08 e do Código de Defesa do Consumidor - Giacomini, Daniel Orfale (2010)
This study aims to investigate the refund of credits to consumers that were excluded or discontinued of purchasing pool agreements, seeking to scrutinize it in light of the recent legislation that regulates purchasing pool agreements in Brazil, Law No. 11795/08, as well as the Consumer Protection Code. At first, the study draws the mechanism of purchasing pool agreements in Brazil, broaching its historical evolution and legal development. Once the mechanism of purchasing pool agreements in Brazil is scrutinized, grounds of consumers defense in analyzed, once, as it deals with a consumer relation, purchasing pool agreements are also subject to the rules set forth in the Consumer Protections Code. Another aspect of the study relates to consumer agreements, provided that purchasing pool agreements are emblematic adhesion contracts. It is also necessary to analyze purchasing pool agreements, identifying its parties, ground concepts and main characteristics, emphasizing Brazilian Central Bank s attribution to regulate and supervise such agreements, as well as to determine the ground conditions of purchasing pool agreements, as provided for in respective bills. Once this scenario is drew, the ground is set to present the argumentation concerning refunding of amounts paid by consumers that were excluded or discontinued of purchasing pool agreements. Before the recent legislation, such topic caused disagreement among Court decisions and legal writers, with sound arguments, economical and legal, both to sustain that refund should occur immediately or that the refund should occur upon termination of the purchasing pool, dully updated. The actual rules concerning refund of amounts is then scrutinized, considering that according to Law No. 11795/08 there is no need to wait termination of the purchasing pool in order to refund the amounts due to consumers, as excluded and discontinued consumers take part in the raffle in order to be reimbursed immediately. The study carried on resulted in the conclusion that Law No. 11795/08 adopted the stand that the general interest of all the individuals that take part in the purchasing pool should prevail over the interest of one single consumer. To that extent, the Law No. 11795/08 is in line with rule of reason and the principle of harmony, as it conditioned the refund of amounts to the rule of raffle, which is proper to purchasing pool mechanisms, as it was conceived